PARADIGMA PENELITIAN TAFSIR AL-QUR’AN DI INDONESIA - Gusmian, Islah (IAIN Kediri, 2015)
Studies on the works of Quranic exegesis (kitÃ„Âb al-tafsÃ„Â«r) as developed in literatures have been so far orientedÃ‚Â to unveil technical aspects, methods, and characteristics of the works. Works by al-FarmÃ„ÂwÃ„Â«, Yunan Yusuf,Nasrudin Baidan, for example, share a common tendency in their approaches. Despite of the importance of suchÃ‚Â works, the current studies on the works of tafsÃ„Â«r are still lack of a comprehensive methodology that enablesÃ‚Â us to figure out epistimelogical and socio-cultural landscapes of a certain work on tafsir. Using a criticalÃ‚Â discourse analysis and epistemÃƒÂ© of journalistic writing model as the basis, this paper attempts to develop a newÃ‚Â paradigmatic construction by which any interests, discourses, ideologies and oppositional spirits against sociopoliticalÃ‚Â facts in tafsÃ„Â«r works are revealed.Keywords: Tafsir, Analisis Wacana Kritis, Teks Kultural